Different Clinical Characteristics Among Aeromonas hydrophila, Aeromonas veronii biovar sobria and Aeromonas caviae Monomicrobial Bacteremia - Chuang, Han-Chuan (The Korean Academy of Medical Sciences, 2011)
This study aimed to compare the clinical presentations of Aeromonas hydrophila, A. veronii biovar sobria and A. caviae monomicrobial bacteremia by a retrospective method at three hospitals in Taiwan during an 8-yr period. There were 87 patients with A. hydrophila bacteremia, 45 with A. veronii biovar sobria bacteremia and 22 with A. caviae bacteremia. Compared with A. hydrophila and A. veronii biovar sobria bacteremia, A. caviae bacteremia was more healthcare-associated (45 vs 30 and 16%; P = 0.031). The patients with A. caviae bacteremias were less likely to have liver cirrhosis (27 vs 62 and 64%; P = 0.007) and severe complications such as shock (9 vs 40 and 47%; P = 0.009) and thrombocytopenia (45 vs 67 and 87%; P = 0.002). The APACHE II score was the most important risk factor of Aeromonas bacteremia-associated mortalities. The APACHE II scores of A. caviae bacteremias were lower than A. hydrophila bacteremia and A. veronii biovar sobria bacteremia (7 vs 14 and 16 points; P = 0.002). In conclusion, the clinical presentation of A. caviae bacteremia was much different from A. hydrophila and A. veronii biovar sobria bacteremia. The severity and mortality of A. caviae bacteremia were lower than A. hydrophila or A. veronii biovar sobria bacteremia.